2015
DOI: 10.1038/ncomms7946
|View full text |Cite
|
Sign up to set email alerts
|

Mouse oocytes depend on BubR1 for proper chromosome segregation but not for prophase I arrest

Abstract: Mammalian female meiosis is error prone, with rates of meiotic chromosome missegregations strongly increasing towards the end of the reproductive lifespan. A strong reduction of BubR1 has been observed in oocytes of women approaching menopause and in ovaries of aged mice, which led to the hypothesis that a gradual decline of BubR1 contributes to age-related aneuploidization. Here we employ a conditional knockout approach in mouse oocytes to dissect the meiotic roles of BubR1. We show that BubR1 is required for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
65
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 62 publications
10
65
2
Order By: Relevance
“…28 The mild rescue effects by AurkB/C inhibition on correct KT-MT attachment in DKO oocytes are similar to the phenomena in the BubR1 knock out oocytes, so we speculate that BubR1 can recruit PP2A to specific locations in ooplasm. Whether cytosolic PP2A, other than KT-localized PP2A, can regulate the formation of KT-MT attachment during meiotic maturation, remain to be addressed.…”
Section: Pp2a Is Essential For Chromosome Alignment and Spindle Formasupporting
confidence: 60%
See 1 more Smart Citation
“…28 The mild rescue effects by AurkB/C inhibition on correct KT-MT attachment in DKO oocytes are similar to the phenomena in the BubR1 knock out oocytes, so we speculate that BubR1 can recruit PP2A to specific locations in ooplasm. Whether cytosolic PP2A, other than KT-localized PP2A, can regulate the formation of KT-MT attachment during meiotic maturation, remain to be addressed.…”
Section: Pp2a Is Essential For Chromosome Alignment and Spindle Formasupporting
confidence: 60%
“…Previous studies have shown that PP2A can be recruited to KTs to facilitate correct KT-MT attachments formation both in mitosis and meiosis. 14,[26][27][28] However, how PP2A regulate KT-MT attachments in oocyte meiosis I remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…To test for SAC involvement oocytes were matured in Endo-FF and reversine, an Mps1 kinase inhibitor used previously to overcome the SAC30313233. Oocyte maturation was significantly increased by 20% following reversine addition (68% vs 48%, P = 0.0074; Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Without the SAC, mitosis is accelerated and chromosome missegregation occurs41. Results obtained in mouse oocytes demonstrate that loss of SAC components leads to strong acceleration of meiosis I, severe chromosome missegregations and sterility424344. However, the SAC is not very efficient in meiosis, compared with mitosis, and the presence of one or few incorrectly attached kinetochores with reduced IKT tension escapes checkpoint detection in mouse oocytes244546.…”
mentioning
confidence: 99%